OP0053 Success-1 in osteoarthritis (oa) trial: celecoxib significantly reduces risk of serious upper gi complications compared to nsaids while providing similar efficacy in 13, 274 randomised patients. (1st June 2001) - Singh, G; Goldstein, J; Bensen, W; Agrawal, N; Eisen, G; Fort, J; Bello, A; Boots, S
Abstract : Background: SUCCESS-1, the largest double-blind, randomised study in rheumatology, compared 2 therapeutic doses of celecoxib to conventional doses of NSAIDs in a trial designed to closely parallel clinical practice in various worldwide settings. Objectives: To compare the efficacy, safety, and tolerability of celecoxib 200 or 400 mg/d and NSAIDs in OA of the knee, hip, and hand. Methods: SUCCESS-1 enrolled 13, 274 patients with OA from 1142 centres in 39 countries. Patients were randomised to: celecoxib 200 mg/d, celecoxib 400 mg/d, or NSAID (naproxen 100 mg/d in US/Canada, diclofenac 100 mg/d in other 37 countries). Efficacy assessments, stratified by country/subregion, included patient and physician global assessments, pain scale, night pain, and WOMAC. An independent Gastrointestinal Events Committee (GEC) categorised potential clinically significant upper GI (UGI) events in a blinded fashion as ulcer complications (perforations, gastric outlet obstruction, bleeding) or symptomatic ulcerations. Results: Of 13, 194 patients treated, 4393 and 4407 received 200 or 400 mg/d of celecoxib, respectively, 905 received naproxen 1000 mg/d, and 3489 received diclofenac 100 mg/d. Most patients were female (67%); mean age was 62 years. Baseline aspirin use and UGI bleeding history were comparable. Efficacy results between the 2 celecoxib doses and naproxen or diclofenac were comparable for most countries/subregions. UGI events (dyspepsia, abdominal pain, and nausea) were significantly reduced in celecoxib- compared to naproxen- or diclofenac-treated patients. Of 144 possible serious UGI GEC-referred events, 9 met strict ulcer complication definition and 36 patients had confirmed ulcer complications and/or symptomatic ulcers. Conclusion: Compared to conventional NSAIDs, celecoxib reduced the risk of ulcer complications by almost 87.5%, while providing equivalent efficacy and better tolerability. Sponsored by Pharmacia Corporation and Pfizer Inc.